P037 Bacterial handling defect in macrophages of patients with defects in glucose-6-phosphate metabolism and Crohn's disease like intestinal inflammation. (16th January 2018) - Pandey, S; Balagopal, K; Aschenbrenner, D; Capitani, M; Weidinger, C; Pires, E; McCullagh, J; Travis, S; Ziegler, J; Siegmund, B; Uhlig, H H
Abstract: Background: Aberrant innate bacterial handling is one of the key mechanisms underlining Crohn's disease (CD). Recently, in several inflammatory disorders defects in immunometabolism have been described but it is not clear whether this is a primary or secondary effect. Several monogenic immunodeficiencies that affect phagocyte activity present as Mendelian disorder associated inflammatory bowel disease. One intriguing subgroup is the group of patients with Glycogen storage disease type Ib (GSD-Ib) and congenital neutropenia. These patients have defective Glucose-6-phosphate metabolism caused due to genetic mutation in Glucose-6-phosphatase b and Glucose-6 phosphate-translocase (G6PT) and a subgroup develops CD-like intestinal inflammation. Methods: We used cholorogenic acid as Glucose-6 phosphate-translocase inhibitor to model Glucose-6 phosphate-translocase defects in primary human monocyte derived macrophages. To investigate the bacterial handling, we performed gentamicin protection assay on healthy and patient primary monocyte derived macrophages. mTOR activation was monitored by S6-phos-Flow. We performed sea-horse assay and metabolomics by LC-MS to monitor the metabolic status of macrophages treated with cholorogenic acid. Results: Chemical inhibition of G6PT in monocyte derived macrophages and patient derived macrophages showed decreased Salmonella typhimurium clearance. Decreased Salmonella killing was associated with activation of mTOR signalling whereas blockade of mTOR signalling using rapamycin reversed the defective bacterial handling. Metabolic profiling of macrophages shows rewiring of the metabolic status skewed towards increased glycolysis. In accordance with this finding is that macrophages treated with G6PT inhibitor showed increased glycolytic extracellular acidification rate in the sea-horse assay in comparison to controls. Conclusions: Our study suggests that an altered metabolic status due to a defect in glucose metabolism in macrophages can cause defective bacterial handling. This adds to the growing evidence that modulation of immunometabolism can have an important impact on inflammatory disorders, a finding relevant beyond monogenic disorders.